A Five Year Study: Prevalence and Antibiotic Resistance Profiles of Gram Negative Bacilli Associated with Urinary Tract Infections (UTIs) in Karachi, Pakistan - Jabonero, Sharmaine Solis (International Journal of Natural Sciences: Current and Future Research Trends, 2025)
Restricted Access.